Energy, environmental, economic retrofit framework for low-rise office buildings in Shanghai: a multi-objective decision-making approach - Hong, Yuanda (2021)
Office buildings comprise of 25% and also accounts for the most significant energy consumption in the commercial building sector in Shanghai. Within this, existing low-rise office buildings (LOBs, below six floors) make up over 50% and are barely adaptable to the present climate variation. On the other hand, it is projected that building energy consumption will increase by 1.7% annually until 2025 along with other reasons. Hence, it is imperative to retrofit these existing LOBs to reduce energy consumption and meet with sustainable building energy use intensity (EUI) standards. However, there is no standard retrofitting framework for this building typology.